Study of the possible causes of post mating reproductive losses in beef cattle farming in Northwest Argentine (Veterinary Science, 2024)
With the purpose of diagnosing the presence of possible causes of reproductive losses, 4 groups of breeding females were surveyed and formed afterthe mated period ended in 5 beef cow-calf ranches (BCR) of Salta province. The in each BCR were: PC, pregnant cows (n=15), PH, pregnant heifers (n=15), NPC, no pregnant cows (n=10) and NPH, no pregnant heifers (n=10). At pregnancy diagnosis, body condition (BC) was recorded and females were sampled fordiagnosis of brucellosis, bovine viral diarrhea virus (BVD), bovine herpesvirus 1, bovine rhinotracheitis (IBR), neosporosis and leptospirosis. Blood Se values and serum Cu, Zn, Mg, Ca and thyroxine (T4) were determined. In the 5 BCRs, a greater (p
Keywords: Breeding cow, survey, abortigenic diseases, mineral profiles, province of Salta.; Breeding cow